Relationship between the elastic modulus of the cage material and the biomechanical properties of transforaminal lumbar interbody fusion: A logarithmic regression analysis based on parametric finite element simulations. (February 2022) - Lu, Teng; Ren, Jiakun; Sun, Zhongwei; Zhang, Jing; Xu, Kai; Sun, Lu; Yang, Pinglin; Wang, Dong; Lian, Yueyun; Zhai, Jingjing; Gou, Yali; Ma, Yanbing; et al.
Highlights: The relationship between cage- E and the biomechanical properties of TLIF was successfully determined based on logarithmic regression and finite element analyses. The established functional equations provide a way to directly guide the rapid development and optimization of novel cage materials. As cage- E increased from 0.1 to 110 GPa, the risks of cage subsidence and pseudarthrosis and the mechanical requirement of the cages decreased, whereas the risk of instrumentation failures simultaneously increased. Abstract: Background and objective: Conventional method for evaluating the biomechanical effects of a specific elastic modulus of cage (cage- E ) on spinal fusions requires establishing a "one-on-one" biomechanical model, which seems laborious and inefficient when dealing with the emergence of numerous cage materials with various cage- E s. We aim to offer a much convenient method to instantly predicting the biomechanical effects of any targeted cage- E on transforaminal lumbar interbody fusion (TLIF) by using a parametric finite element (FE) analysis to determining the regression relationship between cage- E and biomechanical properties of TLIF. Materials and methods: A L4/5 FE TLIF construct was modeled. Cage- E was linearly increased from 0.1 GPa (cancellous bone) to 110 GPa (titanium alloy). The function equations for assessing the influence of cage- E on the biomechanical indexes of TLIF were established using a logarithmic regression analysis. Experimental results: As cage- E increased from 0.1 GPa to 110 GPa, all the biomechanical indexes initially increased or decayed rapidly, and then slowed over time. Logarithmic regression models and functional equations were successfully established between cage-E and these indexes (P<0.0001). Their determination coefficients ranged from 0.72 to 0.99. The range of motions decreased from 0.37–1.10° to 0.20–1.07°. The mean stresses of the central and peripheral grafts reduced from 0.10–0.41 and 0.25–0.42 MPa to 0.03–0.04 and 0.19–0.27 MPa, respectively. In addition, the maximum stresses of the screw-bone interface and posterior instrumentation reduced from 11.76-25.04 and 8.91–84.68 MPa to 9.71–18.92 and 6.99–70.59 MPa, respectively. Finally, the maximum stresses of the cage and endplate increased from 0.28-1.35 MPa and 3.90–8.63 MPa to 14.86–36.16 MPa and 11.01–36.55 MPa, respectively. Conclusions: The decrease of cage- E reduces the risks of cage subsidence, cage breakage, and pseudarthrosis, while increasing the risk of instrumentation failure. The logarithmic regression models optimally demonstrate the relationship between cage- E and biomechanical properties of TLIF. The functional equations based on these models can be adopted to predict the biomechanical effects of any targeted cage- E s on TLIF, which effectively simplifies the procedures for the biomechanical assessments of cage materials.